The effect of the polyadenylation inhibitor Cordycepin on MCF-7 cells - Khurshid, Asma (2015)
Cordycepin (3′-deoxyadenosine) is a medicinal bioactive component of the caterpillar fungi (Cordyceps and Ophicordyceps). It is reported to have nephroprotective, antiapoptotic, anti-metastatic, hepatoprotective (Yue et al. 2013), inflammatory effects, antioxidant, anti-tumor, immunomodulatory and vasorelaxation activities. Cordycepin is well known to terminate and inhibit polyadenylation, both in vitro and in vivo. Other proposed mechanisms of action of cordycepin include activation of adenosine receptors, activation of AMP dependent kinase (AMPK) and inhibition of PARP1. The purpose of this study is to elucidate the biological and pharmacological effects of cordycepin on cancer cell lines such as MCF-7 cells. In this study I found that cordycepin reduces the cell proliferation in all examined cell lines without always exerting an effect on 4EBP phosphorylation and protein synthesis rates. Therefore, the effects on protein synthesis via inhibition of mTOR, which were previously reported, are not only the sole reason for the effect of cordycepin on cell proliferation. Knockdown of poly (A) polymerases reduces cell proliferation and survival, indicating that poly (A) polymerases are potential targets of cordycepin. I studied different adenosine analogues and found that 8 aminoadenosine, the only one that also consistently inhibits polyadenylation, also reduces levels of P-4EBP. It also inhibits the expression of specific genes indicating that the effects on polyadenylation, mTOR signalling and gene expression are linked. Also consistent with polyadenylation inhibition as the major mode of action is the fact that the effects of cordycepin on gene expression are predominantly post-transcriptional. However, knockdown of poly (A) polymerases did not have the same effects on gene expression or on polyadenylation, indicating that cordycepin may act as a dominant negative rather than as a null mutant. This is consistent with the fact that cordycepin is known to arrest a normally transient polyadenylation complex. We performed microarray analysis of cordycepin treated MCF-7 cells and found that the downregulated mRNAs were predominantly involved in transcriptional regulation, cell proliferation, cell cycle and cell migration. These data show that cordycepin is a promising new drug for cancer and indicates that the mode of action it is likely to be through the inhibition of polyadenylation.